Effects of Cultivation Conditions on the Expression Level of Recombinant scFv Antibody against EpEX in Escherichia coli - Mohammadi Vadoud, Seyyed ali; Hashemi, Atieh; keramati, Malihe; Rasouli Kery Bozorg, Farideh (Trends in Peptide and Protein Sciences, 2019)
The EpCAM (epithelial cell adhesion molecule) is a cell surface antigen over expressed in many types of epithelial cell cancers including colon, stomach, pancreas, lung, ovarian, and breast. So, it can be an attractive target for active and passive immunotherapy of cancers. ScFv (single chain fragment variable) fragment is a class of engineered antibodies in which the genes coding for the heavy (VH) and light chains (VL) of an immunoglobulin have been linked with a short flexible peptide linker. Inexpensive media, rapid growth rates, and relatively minimal laboratory set up make Escherichia coli (E. coli) a suitable host for expression of a large variety of recombinant proteins. Here, we assessed the effect of cultivation conditions on the level of expressed scFv against extracellular domain of EpCAM (EpEX) in E. coli. pET22b-antiEpEX-scFv was transformed into prepared E. coli Rosetta™(DE3) competent cells. To evaluate the effect of cultivation conditions on protein expression level, three factors of incubation temperature (25, 30, 37°C), the IPTG (isopropyl-β-D-thiogalactoside) concentration (0.1, 0.25, 0.5, 1 mM), and induction duration (3, 5, 7, 18 h) were considered. SDS-PAGE and western blot analysis demonstrated an estimated 30 kDa-size protein band which was related to the recombinant scFv expressed in E. coli Rosetta™(DE3) strain. At optimal condition (5 h after induction with 0.5 mM IPTG at 25 °C), the final production yield of the antiEpEX-scFv was 403.29 ± 87.50 μg/mL. Our results provide a foundation for the development of scFv-based drugs’ production as effective therapeutic agents in cancers with epithelial origin. HIGHLIGHTS The antiEpEX-scFv was successfully expressed in E. coli Rosetta™(DE3) strain. The highest concentration of protein was obtained with 0.5 mM IPTG at 30°C. The final yield of recombinant antiEpEX-scFv was approximately 403.29 ± 87.50 mg/L.